The impact of building information modelling (BIM) maturity and experience on contractor absorptive capacity. (3rd September 2018) - Ahankoob, Alireza; Manley, Karen; Hon, Carol; Drogemuller, Robin
ABSTRACT: Building information modelling (BIM) has been adopted with increasing frequency by the construction industry in the last few years due to its potential to enhance construction business performance. While there is a general belief that higher BIM proficiency will lead to higher business performance, few empirical studies have tested this relationship. This research explores the extent to which a positive relationship exists between BIM adoption and organisational learning. The impact of BIM maturity and years of experience on the absorptive capacity (AC) of contractors to adopt new information for organisational learning is investigated through a survey of Australian building contractors. While BIM experience was found to be a significant predictor for contractor AC, the analysis of variance showed no significant relationship between BIM maturity and AC. The literature indicates a pervasive belief in a potent relationship between BIM maturity and organisational learning, yet it seems that factors traditionally viewed as more peripheral play a bigger role than expected in determining the impact of BIM on learning and business performance. Subsequent interviews found that (1) poor business ties, (2) willingness to share information and (3) organisational cultural values weaken the expected relationship between BIM maturity and AC. The results suggest that the extent of an organisation's experience with BIM is a greater predictor of learning performance than the complexity of BIM usage within the organisation. The main contribution of this paper is to reveal the complexity surrounding the relationship between BIM and business performance.